2019
DOI: 10.3390/w11071423
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Soil Moisture Variations in Different Vegetation Cover Types in Karst Areas of Southwest China: A Plot Scale Case Study

Abstract: For different vegetation types, soil moisture content shows varying characteristics in different seasons and under different precipitation conditions. However, these characteristics have not been extensively analyzed in karst regions of southwest China. In this study, the soil moisture content of four plots of bare land, grassland, shrubland, and forestland was monitored, and the soil moisture content and corresponding meteorological data for each plot were analyzed. The results indicate that the average soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…For example, Yang et al (2021) found that under the same rainfall conditions, the response time of grassland soil moisture to rainfall is shorter than that of the soil moisture of farmland and bare land and that the sensitivity of soil moisture in grassland is higher than that in farmland and bare land. Zhou et al (2019) found that with the increase in rainfall, the increase in the soil water content in forestland and shrubland is greater than that in bare land and grassland. These studies have also explained the response process of the soil moisture of different vegetation types to rainfall in terms of response degree and response time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yang et al (2021) found that under the same rainfall conditions, the response time of grassland soil moisture to rainfall is shorter than that of the soil moisture of farmland and bare land and that the sensitivity of soil moisture in grassland is higher than that in farmland and bare land. Zhou et al (2019) found that with the increase in rainfall, the increase in the soil water content in forestland and shrubland is greater than that in bare land and grassland. These studies have also explained the response process of the soil moisture of different vegetation types to rainfall in terms of response degree and response time.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was conducted in the Guangxi Zhuang Autonomous Region (hereinafter referred to as Guangxi). The shallow soil layer and its poor water holding capacity in Guangxi results in a complex runoff generation and confluence, thereby causing frequent regional floods and droughts for many years [23]. Studying the characteristics and risks of regional droughts in this region is thus urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have studied the temporal variation trends of soil moisture and its influencing factors. For example, based on the "space series instead of time series" method, Zhou et al highlighted that the succession of grassland to shrub and woodland would decrease the soil moisture content, and the shrubland is characterized by a more robust soil water conservation capacity than other land types in dry seasons [9,10]. Fu et al found that the soil moisture content of natural forestland was higher than that of abandoned and sloping farmlands, and the artificial forestland exhibited the lowest soil moisture content [11].…”
Section: Introductionmentioning
confidence: 99%